Perception on the Usage of Information Communication Technology for Ecotourism Development in Nigeria - Oyebode, Adegboyega; Adeyemo, Adebisi Ilesanmi; Oladeji, Sunday Oladipo (Journal of Tourism Management Research, 2022)
This study aimed to assess the perception of tourists on the usage of information and communication technology at Old Oyo National Park, Ikogosi Warm Spring Resort and Lacampagne Tropicana by using structured questionnaire directed at 384 tourists randomly; 20 tourists at Old Oyo National Park, 150 tourists at Ikogosi Warm Spring Resort and 214 tourists at Lacampagne Tropicana. Data was analyzed and presented descriptively using tables and inferentially using one way analysis of variance (ANOVA). Results indicated that the tourists mostly made use of internet and social media at the sites. The tourists also perceived that the use of Information Communication Technology would be an innovative approach to solving some of the problems of sustainable tourism development and that use of Information Communication Technology has made work easier and faster. Furthermore, the study indicated significant differences in some socio-demographic characteristics as well as perception on the usage of ICT at the sites (P<0.05). Management of ecotourism sites should therefore create more awareness on the usage of other forms of information communication technology at their sites so as to further enhance tourists’ satisfaction.